Polygenic risk in familial breast cancer: Changing the dynamics of communicating genetic risk. Issue 1 (5th July 2021) - Gregory, Gillian; Das Gupta, Kuheli; Meiser, Bettina; Barlow‐Stewart, Kristine; Geelan‐Small, Peter; Kaur, Rajneesh; Scheepers‐Joynt, Maatje; McInerny, Simone; Taylor, Shelby; Antill, Yoland; Salmon, Lucinda; Smyth, Courtney; et al.
Abstract: Hereditary breast cancer is associated with known genetic changes: either variants that affect function in a few rare genes or an ever‐increasing number of common genomic risk variants, which combine to produce a cumulative effect, known as a polygenic risk (PR) score. While the clinical validity and utility of PR scores are still being determined, the communication of PR is a new challenge for genetic health professionals. This study investigated how PR scores are discussed in the familial cancer clinic compared with a previous study assessing the communication of monogenic risk (MR) for breast cancer. Sixty‐five PR consultations between genetic health professionals and women at familial risk of breast cancer were audiotaped, transcribed, and coded using a methodology adapted from the MR study. Analysis of consultations shows that while there were similarities in communicating MR and PR, the complexity and novelty of the polygenic information influenced the style of counseling used by genetic health professionals toward a teaching model of genetic counseling, rather than a patient‐centered approach. In particular, compared to MR consultations, in PR consultations significantly fewer counselees (a) were asked about their reasons for attending genetic counseling; or (b) had their information preferences, decision‐making style, medical knowledge, understanding, or concerns checked. In conclusion, it is anticipated that PR scores will become part of standard clinical practice. Thus, it will be important for all genetic health professionals to be appropriately educated so that they can tailor their communication to meet patient needs. Abstract :